Mammary Organoids and 3D Cell Cultures: Old Dogs with New Tricks - Sumbal, Jakub; Budkova, Zuzana; Traustadóttir, Gunnhildur Ásta; Koledova, Zuzana (Journal of mammary gland biology and neoplasia, 2020)
3D cell culture methods have been an integral part of and an essential tool for mammary gland and breast cancer research for half a century. In fact, mammary gland researchers, who discovered and deciphered the instructive role of extracellular matrix (ECM) in mammary epithelial cell functional differentiation and morphogenesis, were the pioneers of the 3D cell culture techniques, including organoid cultures. The last decade has brought a tremendous increase in the 3D cell culture techniques, including modifications and innovations of the existing techniques, novel biomaterials and matrices, new technological approaches, and increase in 3D culture complexity, accompanied by several redefinitions of the terms "3D cell culture" and "organoid". In this review, we provide an overview of the 3D cell culture and organoid techniques used in mammary gland biology and breast cancer research. We discuss their advantages, shortcomings and current challenges, highlight the recent progress in reconstructing the complex mammary gland microenvironment in vitro and ex vivo, and identify the missing 3D cell cultures, urgently needed to aid our understanding of mammary gland development, function, physiology, and disease, including breast cancer.
Keywords: buněčná diferenciace; mléčné žlázy zvířat; buněčné sféroidy; Humans; kokultivační techniky; Mammary Glands, Animal; Extracellular Matrix; Female; epitelové buňky; extracelulární matrix; lidé; modely u zvířat; zvířata; myši; Mammary Glands, Human; Mice; Coculture Techniques; Spheroids, Cellular; Breast Neoplasms; Epithelial Cells; ženské pohlaví; Cell Differentiation; Organoids; nádory prsu; organoidy; Models, Animal; mléčné žlázy lidské; Animals; Cell Culture Techniques; buněčné kultury